Evaluation of shear strength parameters of sustainable utilization of scrap tires derived geo-materials for civil engineering applications - Amin, Hamza; Khan, Beenish Jehan; Ahmad, Mahmood; Hakamy, Ahmad; Sikandar, Muhammad Ali; Sabri Sabri, Mohanad Muayad (Frontiers in Earth Science, 2023)
The devastation caused by the illegal dumping and burning of tires has been staggering. In civil engineering, the use of tires engineering properties has become a major concern. For this investigation, the research used locally sourced tire chips and sand. Use tire chips sand as an alternative backfill material that requires less pressure and has more improved properties than traditional backfilled. Four specimens were utilized in this experiment: pure sand and sand mixtures containing 20 percent, 30 percent, and 40 percent tire chips, respectively. Both the Direct Shear and Triaxial Apparatus, two of the most important geotechnical tools, were used to compare and evaluate soil and sand tire chip shear properties. 50, 100, and 150 kPa Confining pressure and normal stress have been utilized to maintain a consistent stress level. Direct shear apparatus had a circular shape with an area of 16.62 cm2 and Triaxial shear apparatus had a height of 7.2 cm and a diameter of 3.2 cm. The stress-strain behavior of both apparatuses under ordinary loading and deviatoric stress was reported. The angles of internal friction (Φ') and cohesion (c') were measured for both equipment and specimens with and without tire chips, and the failure planes for direct shear and triaxial tests were reported. In both the direct and triaxial shear tests, 30 percent of the tire chips sand exhibit the best results, respectively. The toughness of soil may be significantly improved by the addition of tire chips.